2022
DOI: 10.3389/fpls.2022.833858
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Waves Regulate Antioxidant Defense and Gluconeogenesis to Improve Germination From Naturally Aged Soybean Seeds

Abstract: Soybean seeds contain substantial triacylglycerols and fatty acids that are prone to oxidation during storage, contributing to the dramatic deterioration of seed vigor. This study reports an ultrasonic waves treatment (UWT), which is a physical method capable of promoting the germination ability of the aged soybean seeds by regulating the antioxidant defense and gluconeogenesis. Germination test revealed that UWT significantly increased the germination rate and seedlings’ establishment of the soybean seeds sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 69 publications
1
2
0
Order By: Relevance
“…Similar results were obtained in this study with high‐density planted wheat, where exogenous SPD application still showed an increase in inferior grain weight, while ETH had the opposite effect (Figure 7). Consistent with Huang et al (2023), exogenous SPD increased SOD activity in wheat grains, but decreased MDA content, thereby maintaining cell membrane stability (Figure S5). Importantly, the enhancement of grain weight by exogenous measures was mainly due to the promotion of the sucrose and starch synthesis pathways in grain weight (Peng et al, 2013; Panda et al, 2016; Teng et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
“…Similar results were obtained in this study with high‐density planted wheat, where exogenous SPD application still showed an increase in inferior grain weight, while ETH had the opposite effect (Figure 7). Consistent with Huang et al (2023), exogenous SPD increased SOD activity in wheat grains, but decreased MDA content, thereby maintaining cell membrane stability (Figure S5). Importantly, the enhancement of grain weight by exogenous measures was mainly due to the promotion of the sucrose and starch synthesis pathways in grain weight (Peng et al, 2013; Panda et al, 2016; Teng et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
“…Metabolomics analysis also showed that, during germination, some plant metabolites, namely γ ‐aminobutyric acid (GABA), riboflavin (vitamin B 2 ), o ‐phosphoethanolamine, and glucose‐6‐phosphate were found to be significantly increased after the germination of red rice 56,84 . A study of soybean seeds corroborated these findings demonstrating that ultrasound significantly upregulated the activity of several key enzymes in gluconeogenesis and the transcription levels of corresponding genes 85 …”
Section: Low‐frequency Ultrasound Treatment Induces Physical and Bioc...mentioning
confidence: 83%
“…56,84 A study of soybean seeds corroborated these findings demonstrating that ultrasound significantly upregulated the activity of several key enzymes in gluconeogenesis and the transcription levels of corresponding genes. 85 The accelerated imbibition stimulates cell metabolism. The sonication of barley (Hordeum vulgare) seeds resulted in near full imbibition (an increase of 96% in seed weight) 44 h after soaking, wileyonlinelibrary.com/jsfa whereas untreated seeds showed a weight gain of only 52%.…”
Section: Low-frequency Ultrasound Treatment Induces Physical and Bioc...mentioning
confidence: 99%